Time effect of elastic energy release of surrounding rock and evaluation method of reasonable advancing speed - Ruifu Yuan; Qi Ma; Qunlei Zhang; Chun Feng; Chunfu Wei; Yan Gao (International Journal of Coal Science & Technology)
Abstract To reveal the rock burst mechanism, the stress and failure characteristics of coal-rock strata under different advancing speeds of mining working face were explored by theoretical analysis, simulation, and engineering monitoring. The relationship between energy accumulation and release was analyzed, and a reasonable mining speed according to specific projects was recommended. The theoretical analysis shows that as the mining speed increases from 4 to 15 m/d, the rheological coefficient of coal mass ranges from 0.9 to 0.4, and the elastic energy of coal mass accumulation varies from 100 to 900 kJ. Based on the simulation, there is a critical advancing speed, the iteration numbers of simulation are less than 15,000 per mining 10 m coal seam, the overburden structure is obvious, the abutment pressure in coal mass is large, and the accumulated energy is large, which is easy to cause strong rock burst. When the iteration number is greater than 15,000, the static force of coal mass increases slightly, but there is no obvious rock burst. Based on engineering monitoring, the mining speed of a mine is less than 8 m/d, and the periodic weighting distance is about 17 m; as the mining speed is greater than 10 m/d, and the periodic weighting distance is greater than 20 m; as the mining speed is 3–8 m/d, and the range of high stress in surrounding rock is 48 m; as the advancing speed is 8–12 m/d, and the high-stress range in surrounding rock is 80 m. Moreover, as the mining speed is less than 8 cut cycles, the micro seismic energy is less than 10,000 J; as the mining speed is 12 cut cycles, the micro-seismic energy is about 20,000 J. In summary, the advancing speed is positively correlated with the micro seismic event; as the mining speed increases, the accumulated elastic energy of surrounding rock is greater, which is easy to cause rock burst. The comprehensive analysis indicates the daily advance speed of the mine is not more than 12 cut cycles.